Upaya Mengatasi Kesulitan Belajar Matematika dengan Media Gambar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
The use of visual media in mathematics learning can help students understand difficult concepts, especially abstract ones. Images allow students to visualize mathematical processes, such as addition and subtraction, making these concepts easier to grasp. Visual media serves as an effective tool for delivering content, particularly in topics like geometry, which are hard to imagine using formulas alone. Additionally, visual media can enhance students' interest and motivation in mathematics, as learning becomes more engaging and enjoyable.